(3GdJdhjM Edi cTa MbGFb GdJfbjMs - (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s ((3Ydi Hf CHj HcQ GdRgGhi s)
(3ChdgG (B:s
(3hHYO Yde GdCUhd GdLGeY Hjf GdeYbhd hGdefbhd CLd eG jJSfe ai EMcGe CMcGe GdTQY hEf cJGH GdJfbjM eY TQMg GdeSei HGdJhVjM cJGH TGed dNdGUI cd eHShW s
(3BNQgG (B:s
(3hJUQjMGJ HGdebUhO , hNJekG ddcJGH Ydi daX hLhO GdYUHI hbO GJab UHjMI jhe GdGKfjf GdJGSY hGdYTQjf ef Pi GdbYOI SfI KeGf hNeSjf hSHYeGFI aQGZ GdHfGf hCSfGf GdCbdGe ef fXe eG LeYJ ef GdhbGYO aGdMeO ddg Ydi fYeg GdYXe hGdUdGI hGdSdGe Yds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HOGjI GdabQGJ HeOGO CMeQs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs